THE EFFECT OF DIFFERENT PLANTING DISTANCES ON THE GROWTH OF Sargassum sp. CULTIVATED AT BOTTOM-OFF IN EKAS BAY, JEROWARU DISTRICT, EAST LOMBOK REGENCY - Nunik Cokrowati; Baiq Regia Gemara Putri; Andre Rachmat Scabra (Jurusan Perikanan dan Kelautan, 2022)
Sargassum sp. is brown algae which contain bioactive compounds such as fucoidan and alginate. Alginates are widely used in the medical, food and gelling industries and stabilizers. In laboratory experiments, Fucoidan can be used as anti-inflammatory, anti-tumour, and anti-viral. This study aims to analyse the effect of different spacing on the growth of Sargassum sp. using the baseline method in Ekas Bay, Jerowaru District, East Lombok Regency. The method used is an experimental method using a Completely Randomized Design (CRD) with a cultivated period of 30 days. The results showed the growth of Sargassum sp. The highest was in treatment E (40 cm) with an average absolute growth of 628 g, specific growth of 3.76%, number of leaves 7843, number of fruits 7413, with 90% Alginate yield. The lowest growth value was obtained in treatment A (20 cm) with an absolute growth value of 392 g, specific growth of 2.78%, number of leaves 5084, number of fruits 5610 with an alginate yield of 57% with an initial planting weight of 100 g. The conclusion of this research is the different spacing of the seaweed Sargassum sp. using the baseline method in Ekas Bay, Jerowaru District, East Lombok Regency had a significant effect on absolute growth, specific growth rate, and several leaves but not significant on the number of fruits.